![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
3个回答
展开全部
原式=(x+y)(x-2y)+3x+3y+x-2y+3
=(x+y)(x-2y)+3(x+y)+x-2y+3
=(x+y)(x-2y+3)+(x-2y+3)
=(x+y+1)(x-2y+3)
=(x+y)(x-2y)+3(x+y)+x-2y+3
=(x+y)(x-2y+3)+(x-2y+3)
=(x+y+1)(x-2y+3)
展开全部
X2-XY-2Y2+4X+Y+3
=(x-2y)(x+y)+(x-2y)+3(x+y)+3
=(x-2y+3)(x+y+1)
=(x-2y)(x+y)+(x-2y)+3(x+y)+3
=(x-2y+3)(x+y+1)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
解:X2-XY-2Y2+4X+Y+3
=(X+2)²-(Y-1)²-XY-Y²-Y
=(X+Y+1)*(X-Y+3)-Y(X+Y+1)
=(X+Y+1)*(X-2Y+3)
=(X+2)²-(Y-1)²-XY-Y²-Y
=(X+Y+1)*(X-Y+3)-Y(X+Y+1)
=(X+Y+1)*(X-2Y+3)
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询